Agrarian transformation and rural community food security in the lower Gangetic basin: A household survey dataset - Ahsan Habib; Md Sayed Uddin; Jalihah Md Shah (Elsevier, 2024)
This data article describes a dataset derived from a comprehensive household survey aimed at understanding the dynamics of agrarian transformation and its impacts on rural community food security within the Lower Gangetic Basin, specifically along the Arial Khan River, Bangladesh. The survey was conducted as part of a doctoral research project and encompasses data collected from 250 households across a defined Mouza within the basin. The dataset provides detailed insights into various dimensions such as household demographics, land ownership and use, agricultural practices and transformations, socio-cultural and environmental factors, power dynamics, food security status, and the strategies employed to enhance food security. The survey employed a structured questionnaire comprising 78 questions distributed across seven distinct sections. Each section aimed to capture specific aspects of the household’s agricultural and food security-related characteristics. Data collection was carried out from September 2023 to March 2024, following ethical guidelines approved by the University Malaysia Sabah, which included obtaining informed consent from all participants.